Horner syndrome associated with necrotizing bacterial pneumonia after SARS-CoV-2 infection - Júnior, Fernando Pivatto; Bottino, Leonardo Grabinski; Santos, Victor Uberti dos (Clinical and Biomedical Research, 2026)
Introduction: We report the case of a 37-year-old man admitted to a tertiary care hospital for severe SARS-CoV-2 infection, who subsequently required mechanical ventilation. During hospitalization, he developed left-sided ptosis, miosis, and anhidrosis, consistent with Horner syndrome. This case illustrates a rare presentation of this condition in adults secondary to necrotizing pneumonia, likely due to involvement of the stellate ganglion, highlighting the importance of recognizing clinical signs and atypical imaging findings in post–COVID-19 complications.